POST PANDEMIC CLASSROOM AND STUDENTS' READINESS FOR THE UTILISATION OF DIGITAL TECHNOLOGIES IN EKITI STATE UNIVERSITY - OSO, SENNY OLUWATUMBI; Ambode , Akinbiyi Benard (Journal of Education and Practice, 2022)
Purpose: Traditionally, face to face approach to teaching and learning had been the system of education adopted in Nigeria but with the emergence of COVID-19 pandemic and the attendant mandatory closure of schools, there was need to shop for new options in order that learning should continue without risks to human and educational standards. The study examined Students' readiness for the utilisation of digital technologies in post pandemic classroom in Ekiti State University in Nigeria. Methodology: The descriptive research design of the survey type was adopted for the study. Questionnaire was used to collect data. Results showed that digital technologies were available for the students' use and the students were ready for the transition from face to face to virtual learning. Results: The students' performance greatly improved as a result of the students' technology skills acquired with the use of the digital technologies. Though COVID 19 negatively affected education globally, Ekiti State University was not so much affected as to neglect the students. Unique Contribution to Theory, Policy and Practice: Teaching and learning was going on hence the recommendation that there should be improvement on the provision and availability of the digital technologies and efforts should be intensified by stakeholders on the training and retraining for better performance